Neue amerikanische Leitlinien zur Hypertonie: neue Konsequenzen für uns? - Schrader, Bastian; Lüders, Stephan; Koziolek, Michael; Haller, Hermann; Schrader, Joachim (DMW - Deutsche Medizinische Wochenschrift, 2018)
Following the publication of the new US guidelines, especially the new classifications of hypertension and the general reduction in treatment targets were discussed worldwide. Applying the US guidelines to a recent German cohort study would in practice lead to a significant increase in the diagnosis of “hypertension” in untreated patients. The number of under-adjusted patients would also increase sharply, increasing more than those predicted in the US Guidelines. Affected by an intensified antihypertensive therapy would be particularly elderly patients, in which adverse drug reactions but also occur more frequently. It seems doubtful whether the massive increase in the diagnosis “hypertension” can improve the supply situation: the opposite effect of avoiding therapists and patients could occur. Determining the individual risk with suitable, evaluated instruments certainly makes sense to treat more targeted patients. More important than new blood pressure limits is a more accurate classification of blood pressure. Repeated self-measurements and ambulatory blood pressure measurement lead to a better selection of patients benefiting from a therapy.
Keywords: Hypertonie-Leitlinien; ELITE-Studie; Prävalenz; antihypertensive Therapie